Features of hyperplastic processes of the endometrium in the presence of arterial hypertension - Zemlianiy, Yaroslav; Zemlyana, Natalie (Journal of Education, Health and Sport, 2023)
Introduction: The relevance of studying endometrial hyperplastic processes (EHP) is due to their prevalence, impact on quality of life and high risk of malignancy. The structure of EHP takes from 20 to 40% in the pathology of reproductive system in women. Objective: To evaluate the clinical and morphological features of hyperplastic processes of the endometrium in the presence of arterial hypertension. Materials and Methods: 96 women with endometrial hyperplastic processes were examined during the study. The first group consisted of 57 women with endometrial hyperplasia with arterial hypertension. The second group included 39 patients with endometrial hyperplasia without arterial hypertension All patients involved in the study, were investigated by ultrasound on the machine "MyLab50" ( «Esaote», Italy) and videohysteroscopy ( «Karl Storz», Germany). Results: In women of perimenopausal and postmenopausal age arterial hypertension was observed significantly more often compared to women of reproductive age (p<0.05). dysmenorrhea (40,4%; p <0.05), metrorrhagia (43,9%; p <0.05) and infertility (45,8 %; p <0.05) were significant more common for women with EHP and concomitant arterial hypertension. There are no significant differences in morphological forms between women with EHP with arterial hypertension and without hypertension. The presence of arterial hypertension had a significant effect on the risk of EHP recurrence (OR=6,0; CI=1,02-35,27; p<0,05). Conclusions: Arterial hypertension was significantly more common in perimenopausal and postmenopausal women. Dismenorrhea, metrorrhagia and infertility were the most common clinical manifestations of EHP in patients with arterial hypertension. The presence of arterial hypertension is a reliable predictor of the occurrence of EHP recurrences during the one year.